HASIL BELAJAR KOGNITIF FISIKA SISWA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI USAHA DAN ENERGI DI KELAS XI SMA N 1 UKUI - Fakhruddin Z; Robiana Robiana; Yennita Yennita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This research aims to describe the results of cognitive learning physics students in the teaching and learningcontextual approach in physics education at SMAN 1 Ukui School. The subject matter of effort and energy.The subjects studied were grade science students totaling 19 people, with the number of students 9 men and10 women. Data collection in this research done at the end of the learning process by conducting tests ofcognitive skills. Data was analyzed using descriptive analysis techniques include absorbed power, learningeffectiveness, student learning and exhaustiveness learning purposes. Data analysis results showed: theaverage absorbed power is 83.7 % with a good category to the category of effective learning effectiveness.Students studying completeness 94.7 % and 85.7 % completeness of learning goals with comprehensivecategories. Thus, application implementation contextual approach Teaching and Learning ( CTL ) in thesubject matter of effort and energy effectively used to study physics at SMAN 1 Ukui.